Nutrients removal from undiluted cattle farm wastewater by the two-stage process of microalgae-based wastewater treatment. (September 2018) - Lv, Junping; Liu, Yang; Feng, Jia; Liu, Qi; Nan, Fangru; Xie, Shulian
Highlights: Cattle farm wastewater was utilized by microalgae without the dilution. C . vulgaris showed a good potential in nutrient removal from undiluted wastewater. The two-stage process was used for C . vulgaris to enhance nutrient removal efficiency. Abstract: Chlorella vulgaris was selected from five freshwater microalgal strains of Chlorophyta, and showed a good potential in nutrients removal from undiluted cattle farm wastewater. By the end of treatment, 62.30%, 81.16% and 85.29% of chemical oxygen demand (COD), ammonium (NH4 + -N) and total phosphorus (TP) were removed. Then two two-stage processes were established to enhance nutrients removal efficiency for meeting the discharge standards of China. The process A was the biological treatment via C . vulgaris followed by the biological treatment via C . vulgaris, and the process B was the biological treatment via C . vulgaris followed by the activated carbon adsorption. After 3–5 d of treatment of wastewater via the two processes, the nutrients removal efficiency of COD, NH4 + -N and TP were 91.24%–92.17%, 83.16%–94.27% and 90.98%–94.41%, respectively. The integrated two-stage process could strengthen nutrients removal efficiency from undiluted cattle farm wastewater with high organic substance and nitrogen concentration.